The effect of championship participation on training intensity and motivation of Pencak Silat student athletes at Semarang State University, Indonesia - Firmansyah, Achmad Alif; Indardi, Nanang (CV Rezki Media, 2025)
Background: Consistent training and high enthusiasm are the keys to an athlete's success in achieving optimal performance. However, among Pencak Silat athletes at Semarang State University (UNNES), there is a decrease in training intensity and enthusiasm when there is no championship agenda. Objectives: The purpose of this study is to analyze the effect of participation in a championship on the training intensity and motivation of Semarang State University Pencak Silat athletes. Methods: This study used a pre-post design with the same subjects (n = 30) and an explanatory quantitative approach to determine the effect of championship participation on training intensity and motivation. Data were collected using a Likert scale questionnaire that has been tested for validity and reliability (α = 0.872). Data analysis was performed using a paired t-test using SPSS. Results: The results showed a significant increase in training intensity from a mean ± SD of 3.12 ± 0.54 (pre) to 3.78 ± 0.49 (post), and training motivation from 3.05 ± 0.61 (pre) to 3.85 ± 0.55 (post), with t(29) = 5.62 and 6.03, respectively, p = 0.004. Cohen's d effect sizes of 1.03 (intensity) and 1.10 (motivation) indicate significant effects. Conclusions: These findings indicate that participation in championships is a significant external motivator in improving the quality of athletes' training. Therefore, championships can be a coaching strategy to maintain sustainable training motivation, a practical implication that this study has clearly demonstrated.